The time to offer treatments for COVID-19. (4th May 2021) - Ngo, Binh T.; Marik, Paul; Kory, Pierre; Shapiro, Leland; Thomadsen, Raphael; Iglesias, Jose; Ditmore, Stephen; Rendell, Marc; Varon, Joseph; Dubé, Michael; Nanda, Neha; In, Gino; et al.
ABSTRACT: Background: COVID-19 has several overlapping phases. Treatments to date have focused on the late stage of disease in hospital. Yet, the pandemic is by propagated by the viral phase in out-patients. The current public health strategy relies solely on vaccines to prevent disease.Methods: We searched the major national registries, pubmed.org, and the preprint servers for all ongoing, completed and published trial results.Results: As of 2/15/2021, we found 111 publications reporting findings on 14 classes of agents, and 9 vaccines. There were 62 randomized controlled studies, the rest retrospective observational analyses. Only 21 publications dealt with outpatient care. Remdesivir and high titer convalescent plasma have emergency use authorization for hospitalized patients in the U.S.A. There is also support for glucocorticoid treatment of the COVID-19 respiratory distress syndrome. Monoclonal antibodies are authorized for outpatients, but supply is inadequate to treat all at time of diagnosis. Favipiravir, ivermectin, and interferons are approved in certain countries.Expert Opinion : Vaccines and antibodies are highly antigen specific, and new SARS-Cov-2 variants are appearing. We call on public health authorities to authorize treatments with known low-risk and possible benefit for outpatients in parallel with universal vaccination.